OVERUSE OF AMONG YOUTH SOCIAL MEDIA INSTAGRAM - Dadang Sudrajat; Taufan Nalendra Pratama; Tegar Yusuf Ardhi Nugraha (SEAN Institute, 2020)
In this era of globalization, technology is increasing advanced, it is undeniable that the presence of the internet is increasing needed in everyday life, both in socialization activities, education, etc. It is undeniable that social media has a great influence on a person's life, including teenagers. Outside, teenagers try to find their identity by hanging out with their peers. This study aims to determine the influence of social media. Explain what the effects of social media are for adolescents in their development, then to find out what are the effects on adolescent behavior caused by social media today, especially in the use of Instagram. In this study, researchers used qualitative research methods because want to explore a fact,